Intellectual skills in higher education - Donald, Janet G. (Canadian Journal of Higher Education, 1985)
The knowledge era has placed new demands on professors and students to analyze and organize information. The intellectual skills required to do this have theoretical forerunners in critical thinking, problem solving, formal operations and creativity. These approaches to intellectual skills are reviewed as well as more recent metacognitive and cognitive approaches. Attempts to teach these skills suggest that they have certain operations in common. A model of intellectual skills is presented which includes the skills of description, selection, representation, inference, synthesis and verification.